DERMATOGLYPHIC AND ANTHROPOMETRIC PROFILE OF THE INDIGENOUS PEOPLE BORARI FROM ALTER-DO-CHÃO VILLAGE IN SANTARÉM-BRAZIL (Fiep Bulletin - online, 2011)
Objective: Identify the anthropometric and dermatoglyphic profile of the indigenous people Boraris (Santarém-Brazil). Methodology: The sample was composed by 24 men and 21 women (n=45, 35.4±19.4 years old). For data collect, the Dermatogliphics protocol (CUMMINS; MIDLO, 1961) has been utilized. The results have been processed through descriptive statistic and the utilization of Excel (Microsoft for Windows – 2007) and Bioestat® 5.0 software. T Student test has been applied for the variation between genders. Results: It was observed that for the anthropometrical measurement, the masculine sex has shown height and body mass mean higher than feminine (masculine: 63.3±17.7 Kg and 1.55±0.14 m; feminine: 57.7±13.8 Kg and 1.48±0.06 m). But the Body Mass Index (BMI) has indicated overweigh among Boraris, mainly in the feminine gender (BMI=26.2±5.9 Kg/m²) than masculine (BMI=25.4±4.7 Kg/m²). However, only the variable height has shown statistic difference (p=0.0092). There was a pattern in the total ridge count of both hands, where RC1>RC2, RC2L (22.2%). Statistics differences between genders haven't been observed (p=0.6843). Conclusion and Recommendation: It can be notice that the sample of indigenous Borari from Alter-do-Chão (Santarém-Brazil) has shown for the anthropometrical variables, overweigh and low height index. For the dermatoglyphic variables have been a predominance of loop draw and also predominance of physical qualities speed and explosive strength. It's been recommended, this way, the realization of similar studies with another ethnics group for characterize them at genetic traces through the dermatoglyphic method.
Keywords: Indigenous people Borarí; Dermatoglyphics; Physical Qualities